IMAGES OF ACADEMIC WRITING ON THE INTERNET AND FOR LITERACY: the case of buy papers’websites - Gonçalves, Kamila (Revista Interface Tecnológica, 2020)
The main objective of this article is to highlight the images of academic writing on websites  that sell papers, such as “Studybay” and “Digital Monographs” to how these images are against the writing images present in the scientific field of ​​the New Literacy Studies area. The referred sites treat writing as a product and are considered as tools to facilitate the writing process. Therefore, in order to analyse these images, the present study will be based mainly on Street (1984, 2001, 2003) and Marcuschi (2000/2001), in addition to texts from Bakhtin's circle that account for the social-historical subject and the collation methodology , in which one statement is placed in comparison to another. During the analysis, clippings will be made on the sites in question, in order to observe the verbal-visual elements and seek, from them, the understanding of the image of writing in that space. In this sense, we start from the hypothesis that there is, in the common sense, the imaginary that writing is difficult, since there are countless websites with academic papers to sell, as welll as several other materials that deal with that theme. It can be said that these sites use this common sense to sell their “product” and perpetuate the idea that writing well is hard. Thus, we believe that this study can provide data to enable the development of solutions to reduce that problem.
Keywords: Academic Writting; Internet; Literacy; Paper Buying’websites; Images